1993
DOI: 10.1021/bi00056a010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mouse heart adenosine 5',5'''-P1-P4-tetraphosphate receptor

Abstract: We have previously demonstrated that mouse brain membrane fractions have a specific, saturable receptor for diadenylated nucleotides. Binding is specific for two adenosines, and the length of the phosphate bridge is critical, with four phosphates being optimal [Hilderman et al. (1991) J. Biol. Chem. 266, 6915-6918]. In this report, we demonstrate that adenosine 5',5"'-P1,P4-tetraphosphate (Ap4A) binding to its receptor is dependent upon an activation step that requires divalent cations and a serine protease. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…A receptor that specifically binds adenine dinucleotides rather than ATP has been isolated from Swiss CDl mice cardiac muscle membranes (Walker et al, 1993b;Hilderman et al, 1994). Unfortunately, no functional study has been carried out to determine what action this receptor mediates.…”
Section: Degradation Of Nucleotides By Atrial Tissuementioning
confidence: 99%
“…A receptor that specifically binds adenine dinucleotides rather than ATP has been isolated from Swiss CDl mice cardiac muscle membranes (Walker et al, 1993b;Hilderman et al, 1994). Unfortunately, no functional study has been carried out to determine what action this receptor mediates.…”
Section: Degradation Of Nucleotides By Atrial Tissuementioning
confidence: 99%
“…As to the type of receptors, there are divergent findings in literature. Hilderman et al identified a unique receptor for diadenosine phosphates ( 13,14), but on the other hand a subtype of purinergic receptors, the P2A receptor, may be activated by diadenosine phosphates (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Our rationale is that the screening of random peptide libraries with mAb TL4, which has been shown to inhibit Ap 4 A binding to its membrane receptor [20,22], should select fusionphage clones whose inserts contain amino acid sequences mimicking the Ap 4 A-binding domain of the receptor. We screened a 15-residue library with mAb TL4 and isolated 24 individual clones whose DNA were sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of the receptor involved in Ap 4 A-mediated cellular signaling is unclear. We have demonstrated in cardiac tissue that Ap 4 A appears to act on a unique dipurinoceptor which is highly specific for Ap 4 A, Ap 5 A, and Ap 6 A (P 2D ) [20]. This receptor undergoes an activation step which enhances only Ap 4 A binding [21].…”
mentioning
confidence: 94%
See 1 more Smart Citation